Model textbook of pakistan studies grade 9 - Naseem kamran (Islamabad National book foundation, 2024)
The Model Textbook of Pakistan Studies for Grade 9 explores the history, culture, geography, and civic structure of Pakistan. It covers important topics such as the ideology of Pakistan, the Pakistan Movement, geographical features, natural resources, and the formation of the state. The book highlights key historical events, national heroes, and the role of Pakistan in the modern world. It aims to build national identity, promote patriotism, and develop critical thinking about social, political, and economic issues.